THE INFLUENCE OF SERVICE BRANDING PERCEPTION ONCUSTOMER SATISFACTION OF LOW COST AIRLINES: AIR ASIA AND MALINDO AIR - Harun, Amran; S. Ashraff, Mohd Nizam; Martin, David; Quantaniah Jusoh, Nur Aniza; Rashid, Umi Kartini (Journal of Technology Management and Business, 2018)
The main challenge of low cost airline such as Air Asia and Malindo Air is to make the brand of the airline echoes with quality. Both airlines are perceived differently even though they are in the same industry due to their branding efforts. Thus, this study aims to understand the relationships of service branding (amenities, word-of-mouth, employee, feelings, reliability and publicity) with customer satisfaction amongst Air Asia and Malindo Air customers. A total of 270 questionnaires were distributed to the customers in the airport through a convenience sampling. The multiple regression analysis indicated only three variables of service branding have significant relationships with customer satisfaction namely amenities, word of mouth and employee. Low cost airlines in general will find this data or information helpful particularly in their endeavour to best serve their customers through service branding efforts which in the long run will help them to sustain and expand their business to another level.Â